Microfinance - Sharma, Manohar (International Food Policy Research Institute, 2003)
Among financial institutions serving poor households around the world, microfinance programs have emerged as important players. These programs typically make small loans—sometimes as small as US$50 to US$100 and sometimes as large as several thousand dollars-to households lacking access to formal-sector banks (see, for example, Lapenu and Zeller 2001). One important achievement of the microfinance movement has been its relative success in deliberately reaching out to poor women living in diverse socioeconomic environments. More than 90 percent of the clients of the Grameen Bank of Bangladesh, perhaps the most well-known microfinance institution worldwide, are women (Khandker, Khalily, and Khan 1996). Of the nearly 189,587 village bank members worldwide that received loans from the Foundation for International Community Assistance in 2001, most are women (FINCA 2002). The Association for Social Advancement (ASA), another prominent microfinance institution in Bangladesh, has a client base of more than 1.5 million persons, out of which 96 percent are women (ASA 2002). In Malawi 95 percent of loans provided by the Malawi Muzdi Fund go to women borrowers (Diagne and Zeller 2001). The microfinance networks led and catalyzed by Women’s World Banking provide direct credit services to more than 12 million poor people around the world. Literally hundreds of similar examples can be found in Africa, Asia, and Latin America.